Homology‐based radiomic features for prediction of the prognosis of lung cancer based on CT‐based radiomics. Issue 5 (16th March 2020) - Kadoya, Noriyuki; Tanaka, Shohei; Kajikawa, Tomohiro; Tanabe, Shunpei; Abe, Kota; Nakajima, Yujiro; Yamamoto, Takaya; Takahashi, Noriyoshi; Takeda, Kazuya; Dobashi, Suguru; Takeda, Ken; Nakane, Kazuaki; et al.
Abstract : Purpose: Radiomics is a new technique that enables noninvasive prognostic prediction by extracting features from medical images. Homology is a concept used in many branches of algebra and topology that can quantify the contact degree. In the present study, we developed homology‐based radiomic features to predict the prognosis of non‐small‐cell lung cancer (NSCLC) patients and then evaluated the accuracy of this prediction method. Methods: Four datasets were used: two to provide training and test data and two for the selection of robust radiomic features. All the datasets were downloaded from The Cancer Imaging Archive (TCIA). In two‐dimensional cases, the Betti numbers consist of two values: b0 (zero‐dimensional Betti number), which is the number of isolated components, and b1 (one‐dimensional Betti number), which is the number of one‐dimensional or "circular" holes. For homology‐based evaluation, computed tomography (CT) images must be converted to binarized images in which each pixel has two possible values: 0 or 1. All CT slices of the gross tumor volume were used for calculating the homology histogram. First, by changing the threshold of the CT value (range: −150 to 300 HU) for all its slices, we developed homology‐based histograms for b0, b1, and b1 /b0 using binarized images. All histograms were then summed, and the summed histogram was normalized by the number of slices. 144 homology‐based radiomic features were defined from the histogram. To compare the standard radiomic features, 107 radiomic features were calculated using the standard radiomics technique. To clarify the prognostic power, the relationship between the values of the homology‐based radiomic features and overall survival was evaluated using LASSO Cox regression model and the Kaplan–Meier method. The retained features with nonzero coefficients calculated by the LASSO Cox regression model were used for fitting the regression model. Moreover, these features were then integrated into a radiomics signature. An individualized rad score was calculated from a linear combination of the selected features, which were weighted by their respective coefficients. Results: When the patients in the training and test datasets were stratified into high‐risk and low‐risk groups according to the rad scores, the overall survival of the groups was significantly different. The C‐index values for the homology‐based features (rad score), standard features (rad score), and tumor size were 0.625, 0.603, and 0.607, respectively, for the training datasets and 0.689, 0.668, and 0.667 for the test datasets. This result showed that homology‐based radiomic features had slightly higher prediction power than the standard radiomic features. Conclusions: Prediction performance using homology‐based radiomic features had a comparable or slightly higher prediction power than standard radiomic features. These findings suggest that homology‐based radiomic features may have great potential for improving the prognostic prediction accuracy of CT‐based radiomics. In this result, it is noteworthy that there are some limitations.